1993
DOI: 10.1016/0014-5793(93)80398-e
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of autophagy‐defective mutants of Saccharomyces cerevisiae

Abstract: A~t~p~a~ in the past is similar to that in mammaIian cells. A mutant designated as apgl ~uto~ha~) defective in adjuration of autophagic bodies in the vacuoles was isolated by selection using a light microscope from a mutagenized proteinase-deficient strain. In the apgl strain, which has normal vacuolar proteinases, nitrogen starvation did not induce protein degradation. The agg;l mutant lost its viability faster than wild-type cells during nitrogen starvation. By using the loss of viability as a first screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
1,292
1
21

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,640 publications
(1,355 citation statements)
references
References 12 publications
13
1,292
1
21
Order By: Relevance
“…Alternatively, aggregates may naturally be degraded by autophagy, although such specific engulfment has never been documented. In contrast, autophagy-defective yeast cells, 8 embryonic stem (ES) cells 12 and embryonic fibroblasts 11 are quite healthy and show no apparent abnormalities under growing conditions. In rapidly dividing cells, abnormal proteins may be quickly diluted even if they are not degraded.…”
Section: Intracellular Clearance By 'Baseline Autophagy': Antidegenermentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, aggregates may naturally be degraded by autophagy, although such specific engulfment has never been documented. In contrast, autophagy-defective yeast cells, 8 embryonic stem (ES) cells 12 and embryonic fibroblasts 11 are quite healthy and show no apparent abnormalities under growing conditions. In rapidly dividing cells, abnormal proteins may be quickly diluted even if they are not degraded.…”
Section: Intracellular Clearance By 'Baseline Autophagy': Antidegenermentioning
confidence: 99%
“…In S. cerevisiae, autophagy mutants are defective in spore formation, 8 while autophagy mutants of D. discoideum are defective in normal multicellular developmental processes such as aggregation formation and fruiting body formation. 9 Premature death from the third larval to pupal stages was reported in D. melanogaster mutants.…”
Section: Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, yeast cells may become extremely useful, because autophagy in yeast is essentially similar to that in mammalian cells (Veenhuis et al, 1983;Baba et al, 1994) and allows the application of molecular genetic procedures in order to identify gene products involved in this process. Complementation studies with yeast mutants deficient in autophagy, obtained by screening on loss of cell viability during nitrogen starvation, have shown the participation of at least 15 different protein components (Tsukada & Ohsumi, 1993), and many more will be identified (Thumm et al, 1994). However, the nature of these proteins is, as yet, unknown.…”
Section: Control By Amino Acids and Hormonesmentioning
confidence: 99%
“…Over the past decade, genetic screens performed in yeast have elucidated many of the molecular components involved in this adaptive response. [1][2][3] More recently, the roles of homologous genes are being explored in multicellular organisms and in cells derived from these organisms. 4 These studies have demonstrated that while autophagy is often induced as part of an adaptive response, induction of autophagy may also lead to cell death.…”
mentioning
confidence: 99%